2022
DOI: 10.1039/d2sc02063g
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium-stabilised transition metal formyl complexes: structures, bonding, and ethenediolate formation

Abstract: Herein we report the first comprehensive series of crystallographically characterised transition metal formyl complexes. In these complexes, the formyl ligand is trapped as part of a chelating structure between a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 63 publications
0
24
0
Order By: Relevance
“…[22][23][24][25] The first structurally characterised formyl complex, [ReCp(CHO)(NO)(PPh 3 )], was reported by Gladysz and coworkers in 1979. [26] We [21] and others [27] have shown that the formyl ligand can be stabilised through resonance with the corresponding oxycarbene structure (Figure 1). [28] Figure 1.…”
Section: Structural Motifs From Co and H -mentioning
confidence: 93%
See 3 more Smart Citations
“…[22][23][24][25] The first structurally characterised formyl complex, [ReCp(CHO)(NO)(PPh 3 )], was reported by Gladysz and coworkers in 1979. [26] We [21] and others [27] have shown that the formyl ligand can be stabilised through resonance with the corresponding oxycarbene structure (Figure 1). [28] Figure 1.…”
Section: Structural Motifs From Co and H -mentioning
confidence: 93%
“…We recently reported reaction of magnesium hydride dimer 28 with a series of metal carbonyl complexes (M = Cr, Mn, Fe, Co, Rh, W, Ir). [21] In all cases, transition metal formyl complexes…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…In our study on ethenediolate formation at Cr-Mg complexes, DFT calculations suggest that direct dimerisation of a putative bis(formyl) intermediate ( 62) is a high energy process (ΔG°> 50 kcal mol À 1 ), strongly suggesting that this mechanism is not in operation (Scheme 12b). [23]…”
Section: Mechanism B: Formyl Dimerisationmentioning
confidence: 99%